A retrospective study of pyometra at five RSPCA hospitals in the UK: 1728 cases from 2006 to 2011. (26th October 2013) - Gibson, A.; Dean, R.; Yates, D.; Stavisky, J.
Abstract : A retrospective cross‐sectional study was used to analyse pyometra cases at five RSPCA Animal Hospitals across the UK from 2006 to 2011. A total of 1728 cases of pyometra were recovered from a female dog outpatient caseload of 78, 469 animals, giving a total prevalence of 2.2 per cent over the study period. There was an annual increase in the incidence of pyometra within the population, while elective ovariohysterectomy caseload has declined. There were variations in breed and age at presentation. Bullmastiffs (P<0.0001), golden retrievers (P=0.001) and dogue de Bordeaux (P=0.008) were over‐represented in the pyometra population when compared with the female dog outpatient caseload. Mean age at presentation was 7.7 years. Some breeds presented at a significantly lower age, including dogue de Bordeaux (mean age 3.3 years) and bullmastiffs (mean age 5.4 years), while others presented as older dogs, including Yorkshire terriers (mean age 9.4 years) and border collies (mean age 10.3 years). Surgical mortality rate at the Greater Manchester Animal Hospital was 3.2 per cent. Pyometra is of significant welfare concern, and also has cost implications, particularly in charity practice. These results serve to highlight this condition so that future change in charity practice caseload can be anticipated and strategies can be directed to improve animal welfare.